The effect of hydraulic damper characteristics on the ride and handling of ground vehicle - Rusli, Farah Zulyana; Ridhuan Siradj, Fadly Jashi Darsivan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this paper, ride quality and handling performance of a vehicle are quantified by the vibration transmitted to the vehicle’s body. A passive suspension is designed to compromise between a good ride comfort and a good handling performance. In the development of modern passenger vehicle, subjective testing is greatly involved. In this study, a quantitative method is used to determine the range of suspension parameter for acceleration, braking, ride comfort and handling performances. The investigation involved a full car model with 7 degrees of freedom and VeDyna software was utilized to simulate the performance of the vehicle when subjected to different road profiles and different handling maneuver. The effect of 3 different nonlinear suspension characteristics towards the ride and handling was investigated. The results show that small damping ratio compromise the vehicle dynamic performance, and high damping ratio gives magnification of vibration to the vehicle. This study shows that by changing the suspension characteristics can greatly affect the comfort of the driver and the performance of the vehicle.